Genotype-phenotype correlation in Fabry disease - Ries, Markus; Gal, Andreas (Fabry disease, 2006)
A disease phenotype may be modulated by genetic and non-genetic modifiers. The correlation between genotype and phenotype is a statistical relationship that predicts a physical trait in a person or abnormality in a patient with a given mutation or a group of similar mutations. Analysis of genotype-phenotype correlations in Fabry disease is complicated by a number of factors, such as the high proportion of private mutations, the large phenotypic heterogeneity associated with the same mutation - both among patients from the same family and among those from unrelated families - and the fact that patients with Fabry disease may develop disease-related complications that are observed with high prevalence in the general population. Genotype-related information about the enzyme structure derived from crystallographic analysis, together with measurement of residual enzyme activity, can be of assistance in predicting the likelihood of a severe or attenuated phenotype. Individual genotypes may have pharmacogenomic implications; for example, the maximum possible clinical response to molecular chaperone therapy might be predicted from the correlation between the amount of residual enzyme activity and the associated clinical phenotype. Female heterozygotes exhibit significant phenotypic variability, which could be better understood given more comprehensive epidemiological data.
Gesehen am 16.05.2019